2016
DOI: 10.20961/bioedukasi-uns.v9i1.3880
|View full text |Cite
|
Sign up to set email alerts
|

Profil Keterampilan Argumentasi Ilmiah Mahasiswa Pendidikan Biologi FKIP UNS pada Mata Kuliah Anatomi Tumbuhan

Abstract: <p class="5abstrak">Lemahnya argumentasi ilmiah mahasiswa dalam pembelajaran telah banyak menjadi perhatian,  terutama   dalam hal mengevaluasi dan mengkonstrak permasalahan dan solusinya.   Penelitian ini bertujuan untuk mengetahui bagaimana profil keterampilan argumentasi ilmiah mahasiswa pada mata kuliah Anatomi Tumbuhan. Penelitian ini merupakan penelitian deskriptif untuk mendapatkan gambaran keterampilan argumentasi mahasiswa semester 3 di Prodi Pendidikan Biologi FKIP UNS melalui tugas tertulis ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 3 publications
1
22
0
10
Order By: Relevance
“…Research on the ability of learners' scientific arguments has been made. The results showed that the ability of the scientific arguments learners is at a low level (Probosari 2016). In general, the level of mastery of argumentation ability of learners between the group as well as individuals is not satisfactory.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Research on the ability of learners' scientific arguments has been made. The results showed that the ability of the scientific arguments learners is at a low level (Probosari 2016). In general, the level of mastery of argumentation ability of learners between the group as well as individuals is not satisfactory.…”
Section: Introductionmentioning
confidence: 85%
“…Many international educational curricula that requires students to be able to participate in the argument, debate, and decision-making on science issues (Dawson & Carson 2017). Argumentation ability to be one of the main objectives of learning science (Probosari, Ramli, Harlita, Indrowati, & Sajidan 2016). Relevant to the statement that scientific arguments are a major component of science education (Cetin 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keterampilan argumentasi menjadi salah satu tujuan utama pembelajaran sains karena siswa yang belajar sains harus mengetahui penjelasan ilmiah mengenai fenomena alam dan menggunakan argumentasi untuk memecahkan masalah sehingga mampu memahami temuan lain yang siswa dapatkan. Siswa yang mengerti sains secara utuh harus memahami bahasa sains dan berpartisipasi secara aktif dalam kegiatan ilmiah seperti observasi dan argumentasi (Probosari, et al, 2016). Keterampilan argumentasi sangat penting untuk dilatihkan di dalam pembelajaran sains sehingga peserta didik memiliki nalar yang logis, pandangan yang jelas dan penjelasan yang rasional dari hal-hal yang dipelajari.…”
Section: Pendahuluanunclassified
“…Students lack confidence in submitting opionions about science materials that they do not understand so the students argumentation ability are low [1]. For this reason, researchers want to implement the argument driven inquiry model learning to try to change the learning patterns of students to improve student's ability to argue.…”
Section: Introductionmentioning
confidence: 99%